Chemical ablation as successful alternative for treatment of incompetent perforators - Cvetanovski, Vlatko; Cimjescikj, Dina; Cvetanovska, Marija; Arsovski, Andreja; Mitevski, Aleksandar (Македонско лекарско друштво = Macedonian medical association, 2023)
Introduction. Superficial venous incompetence (SVI) is the most common cause of lower extremity superficial venous reflux and varicose veins; nonetheless, incompetent perforator veins (PVs) are the most common cause of recurrent varicose veins after treatment, often unrecognized. Current minimally invasive treatment options include ultrasound-guided sclerotherapy (USGS), endovascular thermal ablation (EVTA) with either laser or radiofrequency energy sources, subfascial endoscopic perforator surgery (SEPS) and the relatively new chemical ablation procedure using cyanoacrylate adhesive, which we chose as our primary treatment option for this study, using and comparing the results of two different adhesives. Methods. A retrospective review of a prospectively managed database of chemical ablation as perforator vein treatment performed at a single institution from September 2023 to March 2024 was conducted. The indications for PV treatment were >4 mm in diameter and reflux of >500 milliseconds upon leg compression. Results. A total of 32 patients and 49 limbs presenting PV insufficiency (coexisting with GSV insufficiency in 19 patients) were divided into 2 groups of 16 patients, each group based on the chosen chemical ablation adhesive - VenaBlock and VenaSeal. The VenaBlock group had PV closure rate of 100% immediately intraoperative, at 3 days, 2 weeks, 3 weeks and 1 month from the procedure for each treater perforator. From the VenaSeal group, 13 patients had immediate and continuous treatment success during the follow-up, while in 3 patients there was intraoperatively registered treatment failure (P=0.0127). Conclusion. We find the chemical ablation procedure to be safe and effective for PVs, specifically in the case of using rapid polymerization adhesive. Due to its simplicity and short procedural time, we consider this to be the procedure of choice in case of multiple incompetent PVs present, as well as in significant PV tortuosity.
Keywords: superficial venous incompetence; perforating veins; chemical ablation; VenaSeal; VenaBlock